Effectiveness of a Mixed Martial Arts-Based Training Program in Reducing Obesity and Improving Cardiovascular Health Among Women in Indonesia - Adi Saputra, Surya; Hamni, Septiani Dewi; Shirley , Exie; Knowles, Helen (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. To develop and validate a comprehensive Body Fighter Camp Model and Training Program specifically designed for women in Indonesia, addressing the growing obesity epidemic and its associated health risks. The study aims to create an effective mixed martial arts-based exercise intervention that can simultaneously improve body composition and cardiovascular health. Materials and methods. The research employed a quasi-experimental design with 20 female participants (age range 20-45 years) recruited from the Malang area. The Body Fighter Training Program consisted of 20 sessions over 2.5 months, incorporating 9 different exercise components including High Intensity Interval Training, Body Weight Training, Boxing, Judo, Karate, Tabata, Fitness, Circuit Training, and Crossfit. Participants underwent comprehensive health screenings, and measurements of Body Mass Index (BMI) and blood pressure were taken before and after the intervention. Results. The study demonstrated significant improvements across various health parameters. Obese participants experienced BMI reductions of 5-10 kg/m², while overweight participants showed moderate declines of 3-5 kg/m². Blood pressure outcomes were equally promising, with 85% of participants showing cardiovascular health improvements. Statistical analysis revealed a statistically significant result (p = 0.039), with a moderate effect size and 80% statistical power. The program achieved a 100% completion rate and over 90% success in participants reaching their health goals. Conclusions. The Body Fighter Camp Model provides a promising, culturally appropriate approach to addressing obesity and cardiovascular health among women in Indonesia. By integrating martial arts principles with high-intensity interval training, the program offers an engaging and effective alternative to traditional exercise interventions. The research suggests potential for broader implementation in public health strategies targeting obesity prevention and management.